2016
DOI: 10.3390/ma9110939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acoustic Modulation and Mixed Fuel on Flame Synthesis of Carbon Nanomaterials in an Atmospheric Environment

Abstract: In this study, methane–ethylene jet diffusion flames modulated by acoustic excitation in an atmospheric environment were used to investigate the effects of acoustic excitation frequency and mixed fuel on nanomaterial formation. Acoustic output power was maintained at a constant value of 10 W, while the acoustic excitation frequency was varied (f = 0–90 Hz). The results show that the flame could not be stabilized on the port when the ethylene volume concentration (ΩE) was less than 40% at f = 10 Hz, or when ΩE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Further discussion onto the effect of acoustic perturbation whether direct or indirect interaction toward the jet flame behavior are discuss in this paper. Figure 1 shows the interaction between acoustic responses and flame [53]. This interaction provides linear change with the increasing of number of frequency (f) detest to the flame.…”
Section: Effect Of Acoustic Excitation On Flame Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Further discussion onto the effect of acoustic perturbation whether direct or indirect interaction toward the jet flame behavior are discuss in this paper. Figure 1 shows the interaction between acoustic responses and flame [53]. This interaction provides linear change with the increasing of number of frequency (f) detest to the flame.…”
Section: Effect Of Acoustic Excitation On Flame Characteristicsmentioning
confidence: 98%
“…A liftoff height is a point measured from the centerline distance of the duct exit to the plane of flame stabilization [52][53][54][55][56][57][58][59][60][61][62][63][64][65]. Oh et al, [30] proved the correlation of interaction between flame length and liftoff height during acoustic excitation.…”
Section: Flame Length and Liftoff Heightmentioning
confidence: 99%
“…Taking carbon monoxide, methane and ethylene as examples, this paper studies a mixed gas detection algorithm based on extreme random trees to improve the classification accuracy rate. It can provide mixed gas detection and concentration ratio technical support for industrial production, chemical material production, and the light industry [35][36][37]. This study provides a theoretical reference for the simulation of olfactory algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that CNTs produced by different methods (including chemical vapour deposition and laser ablation) contain metal impurities, mainly Fe, Ni and Co, inside the tubes, which are covered with layers of graphene sheets [19, 20]. Today, most studies reporting preparation of MCNTs ( S1 Table ), seem to have overlooked three important facts.…”
Section: Introductionmentioning
confidence: 99%
“…MCNTs can be either endohedral, i.e., made by encapsulating magnetic nanoparticles, such as iron oxides, into the carbon nanotubes, or exohedral, i.e., made with methods such as electrochemical deposition to attach magnetic nanoparticles on the surface of carbon nanotubes [ 1 , 17 , 18 ]. Previous studies showed that CNTs produced by different methods (including chemical vapour deposition and laser ablation) contain metal impurities, mainly Fe, Ni and Co, inside the tubes, which are covered with layers of graphene sheets [ 19 , 20 ]. Today, most studies reporting preparation of MCNTs ( S1 Table ), seem to have overlooked three important facts.…”
Section: Introductionmentioning
confidence: 99%